PENERAPAN COLLABORATIVE FILTERING PADA SISTEM PEMESANAN MENU KAFE UNTUK MENINGKATKAN CROSS-SELLING BERBASIS ANDROID - Daulah, Rafly Maulana; Sejati, Rr. Hajar Puji (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
Cafes have become an essential part of lifestyle in today's digital era, with increasing customer demand for unique and diverse culinary experiences. This study aims to develop an Android-based cafe menu ordering system by implementing the Collaborative Filtering method to improve cross-selling practices. This system is designed to provide personalized menu recommendations based on customer preferences and behavior. Using previous transaction data, this system can suggest additional products that are relevant to the customer's main order, such as suggesting cakes or snacks with coffee. The implementation of this technology is expected to increase customer satisfaction and transaction value in cafes.